PERKEMBANGAN ANAK PADA TOKOH MONA DAN LISA DALAM KKPK MONALISA KARYA ALYA : TEORI PSIKOLOGI SASTRA - Sari, Neva Atika (Jurnal Pena Indonesia, 2017)
The character of Mona and Lisa have different personalities, it is caused by a different upbringing. At the time of their child more interested in learning and ego they appear in extracurricular basketball. Future development of the children learn to get pleasure and satisfaction of completing a task, especially academic assignments that make children proud of the achievements gained, development of a child is very different depending on the education of the parents. It can be seen in the characters development and the Mona Lisa is in the Small Small-Have Work (KKPK) entitled Monalisa. The method used the descriptive analysis. Data collection techniques, carried out by step reading of KKPK Monalisa work Ayla from beginning to ahir repeatedly, Marking the page KKPK "Monalisa", Typing all the existing data in KKPK "Monalisa" according to the study of psychology literature, it leads to the development children adopted by Norman H. Erikson.